2018
DOI: 10.1111/cup.13264
|View full text |Cite
|
Sign up to set email alerts
|

Bedside diagnosis of lentigo maligna with reflectance confocal microscopy

Abstract: Early diagnosis of lentigo maligna (LM) is both critical and challenging.Attiya Haroon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…In our case, LC‐OCT was able to detect in vivo, in both horizontal and vertical imaging, the main microscopic features typical of LM by showing, in the epidermis and around the hair follicles, the presence of large, bright, roundish, or dendritic atypical cells, with evident nuclei, corresponding to atypical melanocytes with a tendency toward folliculotropism. From our results, some considerations follow: the features observed by LC‐OCT in the horizontal sections are similar to those normally obtained by RCM, 3 , 4 , 5 , 6 , 7 which has been demonstrated to be useful in the non‐invasive diagnosis of LM by showing the characteristic atypical melanocytes mainly distributed around the hair follicles. Compared with RCM, LC‐OCT has a slightly lower resolution (1.3 vs. 0.8 μm, respectively) and a higher penetration depth (~500 vs. ~200 μm).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In our case, LC‐OCT was able to detect in vivo, in both horizontal and vertical imaging, the main microscopic features typical of LM by showing, in the epidermis and around the hair follicles, the presence of large, bright, roundish, or dendritic atypical cells, with evident nuclei, corresponding to atypical melanocytes with a tendency toward folliculotropism. From our results, some considerations follow: the features observed by LC‐OCT in the horizontal sections are similar to those normally obtained by RCM, 3 , 4 , 5 , 6 , 7 which has been demonstrated to be useful in the non‐invasive diagnosis of LM by showing the characteristic atypical melanocytes mainly distributed around the hair follicles. Compared with RCM, LC‐OCT has a slightly lower resolution (1.3 vs. 0.8 μm, respectively) and a higher penetration depth (~500 vs. ~200 μm).…”
Section: Discussionsupporting
confidence: 82%
“…In the past years, the introduction of innovative imaging techniques, especially dermoscopy and reflectance confocal microscopy (RCM), has made a significant contribution in the differential diagnosis of these lesions. [1][2][3][4][5][6][7] Such techniques are able to improve the LC-OCT systems have recently been marketed, and preliminary studies have reported its use in selected cutaneous disorders, including malignant and benign neoplasms [8][9][10][11][12][13][14] and some inflammatory and infectious diseases. [15][16][17][18] We herein present the LC-OCT features of a case of LM involving the nose along with their horizontal and vertical histopathological correlations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, RCM has roughly the same diagnostic power as conventional histology, in addition to the benefits of being completely noninvasive, and allowing repetitive imaging of the same site. Furthermore, some pathologies benefit from the different reflectance of specific structures to facilitate the differential diagnosis of specific pathologies (Zubair et al 2018).…”
Section: Introductionmentioning
confidence: 99%